Surgical treatment of recurrent basal cell carcinoma of parotic-masseteric region with lesion of temporal bone pyramid - V. Ye. Olyushyn; D. A. Gulyayev (Бюллетень сибирской медицины, 2008)
Basal-cellular skin cancer takes the first place accounting for 75—95% of malignant skin tumors. Despite different methods of treatment recurrence rate is up to 39%. Recurrent forms may invade soft tissues, major vessels, nerves and bones of the skull base. Options of surgical treatment of wide-spread recurrent forms are considered in this article. Modified block-resection of parotid-masticatory region along with temporal pyramid invasion is presented. Short- and long-term follow-up results are also presented.